Equity and trusts - Hudson, Alastair (Routledge, 2013)
"Alastair Hudson's Equity and Trusts is an ideal textbook for undergraduate courses on the law of trusts and equitable remedies. It provides a clear, current and comprehensive account of the subject through which the author's enthusiasm and expertise shine through, helping to bring to life an area of the law which students often find challenging.Beginning with the core principles, Professor Hudson reinforces the key